PTPN VIII New Palm Oil Plantation in Kertajaya Banten - Budiarani, Vanesa Hana; Murtaqi, Isrochmani (Journal of Business and Management, 2016)
Abstract.Â Palm oil is one of the main commodities of Indonesia. Every year, Indonesia send thousand tons of palm oils to overseas (export). Hence, palm oil commodities become one of the commodities that become source of devise for Indonesia. PTPN VIII is one of state owned company that produce palm oil as their main commodities. See this big opportunities, PTPN VIII plan to add 1 unit new palm oil plantation in Kertajaya, Banten, where before was tea plantation. This study have aim to know whether project of 1 unit new palm oil plantation in Kertajaya, Banten financially feasible or not. This financial feasibility study using several financial variables approach such as NPV, IRR, WACC,Profitability Index and Payback Period. Beside of that, sensitivity analysis and financial ratios analysis are add to know the sensitivity variables&financial performance of palm oil. The result shown that 1 new palm oil in Kertajaya, Banten is feasible and shows good financial performance, with 2 sensitive variables. In order to improve PTPN VIII performances in the future, PTPN VIII recommended to have guidance and standards to do investment and complete another aspects to being considerate for feasibility study analysis.Keywords: Palm oil, Plantation, Financial Feasibility Study Parameters, Sensitivity Analysis, Financial Ratios Analysis.